CHILD‐CENTERED PLAY THERAPY IN THE SCHOOLS: REVIEW AND META‐ANALYSIS. Issue 2 (12th October 2014) - Ray, Dee C.; Armstrong, Stephen A.; Balkin, Richard S.; Jayne, Kimberly M.
<x xml:space="preserve">Abstract</x> The authors conducted a meta‐analysis and systematic review that examined 23 studies evaluating the effectiveness of child centered play therapy (CCPT) conducted in elementary schools. Meta‐analysis results were explored using a random effects model for mean difference and mean gain effect size estimates. Results revealed statistically significant effects for outcome constructs, including externalizing problems (d = 0.34), internalizing problems (d = 0.21), total problems (d = 0.34), self‐efficacy (d = 0.29), academic (d = 0.36), and other behaviors (d = 0.38). Further, a systematic review was conducted on all studies compared with Outcome Research Coding Protocol criteria. Results indicated that CCPT studies provided quantitative support and qualitatively promising to strong evidence in support of its use in the schools.